The Urgence of Regulation for the Use of Halal Product Labels in the Era of the Industrial Revolution 5.0 - Andi Lala; Sugianto Sugianto (International Journal of Social Service and Research, 2023)
This study aims to analyze the urgency of regulating the use of halal product labels in Indonesia, where halal product labeling is a very important issue, especially in this modern era, namely the era of the industrial revolution 5.0. In addition, this article also aims to identify and analyze whether Law no. 33 of 2014 concerning the Guarantee of Halal Products (UU JPH) there are very serious questions about whether or not in providing constitutional guarantees for the majority of Muslims and especially for minorities in Indonesia. answers and new legal provisions to protect consumers from consuming products that are not halal. This research is based on normative legal research. Normative legal research is research conducted by examining library materials and secondary materials. The approach used in this study uses a normative approach by researching and analyzing the laws and regulations related to halal product guarantees in the 5.0 revolution era and their probes. The normative juridical method takes secondary data through literature study. The results and discussion in the research are first, Labeling of halal products is very important to provide guarantees for consumers to avoid haram properties, especially for Muslims, even for non-Muslims with hygienic goods guaranteed. Guarantees of protection for halal products are contained in the JPH Law, especially in the era of the industrial revolution 5.0 so that this regulation can help provide extra guarantees to consumers regarding the 2 protection of the purchase of halal products. Halal labeling and certification. This is because after the Ministry of Religion of the Republic of Indonesia firmly took over the policy and decision that the MUI was no longer entitled to issue labeling and certification of halal products.